Is Forced Money (Dwangsom) the Key to Enforcing Administrative Court Decisions? Examining Its Impact on Compliance - Chandra, Felisha; Syahwal, Syahwal; Herlambang, Pratama Herry; Akbar, Muhammad (Universitas Negeri Semarang, 2024)
The implementation of forced money (dwangsom) in Indonesia’s administrative courts is a legal tool aimed at ensuring compliance with court decisions, particularly in cases where government bodies fail to fulfill their obligations. This research explores the effectiveness of the dwangsom policy and its implications for improving compliance with administrative court rulings. Using a normative juridical approach, the study analyzes how dwangsom is applied in practice and its impact on the level of compliance by state institutions. The findings reveal that while the dwangsom policy has the potential to encourage compliance, its practical application remains inconsistent. In many instances, government agencies either evade or delay the payment of forced money, leading to minimal impact on ensuring timely enforcement of decisions. The research highlights the need for stricter enforcement mechanisms and greater accountability for public officials who fail to comply with court orders. This study introduces a novel perspective on the role of dwangsom in the broader context of administrative justice in Indonesia. It also addresses the urgency of enhancing its effectiveness to improve the credibility of the administrative courts. The contribution of this research lies in its critical evaluation of the dwangsom policy and its potential for reform. By offering recommendations for strengthening enforcement and compliance, this research aims to contribute to the ongoing discourse on improving the efficiency and accountability of Indonesia's administrative justice system. The findings are particularly relevant to policymakers, legal practitioners, and reform advocates working towards a more responsive legal system.